Zero Hunger and Islamic Philanthropy Movement in Surakarta: A Study at Dahar Gratis Community - Safaah Restuning Hayati (DINIKA : Academic Journal of Islamic Studies, 2023)
Poverty and hunger are significant issues in Indonesia. Non-governmental organizations also participate in poverty alleviation programs through philanthropic actions, including at the local level such as in Surakarta. This study aims to analyses philanthropic practices within the Dahar Gratis Community, Surakarta. The study is qualitative research and employs the theory of creative philanthropy proposed by Helmut K Anheier and Diana Leat (2006), focusing on the charity approach. The findings reveal that the Dahar Gratis Community sparks generosity and solidarity among its members by distributing food to the impoverished, thereby building a periodically empowered society. While operating at the local level, especially among young people, the community strives to provide global influences. The community managers believe that generosity is contagious, inspiring many to follow the same path of sharing with those in need. The Dahar Gratis Community also enhances philanthropic awareness in the community, particularly in Surakarta. This program proves effective in creating positive changes, notably in alleviating hunger and fostering generosity. Achieving a hunger-free society aligns with the Sustainable Development Goals (SDGs) of zero hunger.